Analisis Likuiditas Berbasis Laporan Keuangan BRI Syariah Tahun 2013 – 2015 - Abdul Haris Romdhoni (ITB AAS INDONESIA Surakarta, 2016)
This study aims to examine the liquidity of financial ratios. Liquidity became quite urgent, because liquidity is the ability of a company to meet its obligations in the short term. It was often a problem in some companies or banks. Liquidity for year 2013-2015 BRI Syariah good enough because the current assets by current liabilities are divided proportionally, so that if there is no short-term obligations will be fulfilled by the ratio of current assets are quite liquid.Keywords: liquidity, financial ratios and financial performance